E-Procurement and Procurement Performance of Central Government Procuring and Disposing Entities in Uganda: A Case Study of Kabale Regional Referral Hospital. - Kekitinisa, Privas (Kabale University, 2024)
The study examined e-procurement and Procurement Performance of Central Government Procuring and Disposing Entities in Uganda: A Case Study of Kabale Regional Referral Hospital. The study was guided by three objectives namely; to establish the level of procurement performance in Kabale Regional Referral Hospital, to determine the level of implementation of e-procurement in Kabale Regional Referral Hospital, to establish the relationship between e-procurement practices and procurement performance practice in Kabale regional referral hospital. The study used a descriptive research design that aimed at generating information after the incident had occurred; the Qualitative approach included the use of interviews. Data was collected using a questionnaire and interview guide, and simple random and purposive sampling methods were used. Both qualitative and quantitative methodologies were used to analyze data as a sample size of 59 respondents was used. The study revealed that the level of procurement performance in Kabale Regional Referral Hospital includes; delays in procurement cycles, strategic Sourcing, performance Measurement, open Contracting, and substandard medical supplies. The study revealed the level of implementation of e-procurement in Kabale Regional Referral Hospital and these included, a lack of thorough cost-benefit analysis and effective communication of e-procurement benefits, mixed perceptions about management support, indicating the need for stronger and more consistent leadership, some suppliers may not be fully prepared for e-procurement, highlighting the need for additional support and training, although the ICT infrastructure is deemed adequate by the majority, there is still room for improvement to ensure seamless e-procurement operations. Lastly, the study revealed that the results indicate that enhancing e-procurement practices leads to improved procurement performance, with the effect being both statistically significant and practically relevant. The strength of the relationship, as indicated by the standardized Beta coefficient, is moderate to strong, implying that efforts to improve e-procurement practices can have a substantial positive impact on procurement performance